Pomolic acid: A short review on its chemistry, plant sources, pharmacological properties, and patents - Eric Wei Chiang Chan, Ying Ki Ng, Carine Shu Shien Lim, Vania Septa Anggraeni, Zhi Zhou Siew, Chen Wai Wong, Siu Kuin Wong (Journal of Applied Pharmaceutical Science, 2023)
In this article, the chemistry, plant sources, pharmacological properties, and patents of pomolic acid (PA) are reviewed for the first time. Also known as benthic acid, PA is a pentacyclic triterpenoid of the ursane type. Its chemical structure has a 30-carbon skeleton comprising five six-membered rings A–E with seven methyl groups and two hydroxyl groups. PA was first isolated from the peels of apples. The compound is commonly reported in species of the families Rosaceae and Lamiaceae. Anti-cancer activities represent the major pharmacological properties of PA with breast cancer and leukaemia cells being the most susceptible. A wide array of other pharmacological properties of PA have been reported. PA has two patents filed by the same group of scientists from the Federal University of Rio de Janeiro in Brazil. Some areas for further research on PA are suggested. Sources of information were from Google Scholar, PubMed, PubMed Central, Science Direct, J-Stage, and PubChem.
Keywords: Pentacyclic triterpenoids, benthamic acid, anti-cancer